AB0079 Synovial Explant Inflammatory Mediator Production is Correlated with Disease Activity in Rheumatoid Arthritis: A Cross Sectional Study. (10th June 2014) - Andersen, M.; Boesen, M.; Ellegaard, K.; Christensen, R.; Söderström, K.; Søe, N.; Spee, P.; Mørch, U.G.; Torp-Pedersen, S.; Bartels, E.M.; Danneskiold-Samsøe, B.; Vendel, N.; et al.
Abstract : Background: In vitro assays are widely used for characterisation of rheumatoid arthritis (RA) pathology and for testing of potential disease modifying anti-rheumatic drugs (DMARDs). However, little is known to what extent in vitro disease activity measures are correlated with in vivo disease activity. Objectives: The aim of this study was to investigate whether the release of interleukin 6 (IL-6), interleukin 8 (IL-8), monocyte chemoattractant protein 1 (MCP-1) and macrophage inflammatory protein 1 beta (MIP-1b) correlated with serum c-reactive protein (CRP), tender joint count (TJC, 28 joints), swollen joint count (SJC, 28 joints) and disease activity score of 28 joints (DAS-28-CRP) of RA patients. Methods: Forty synovial sites from the hand joints of sixteen RA patients scheduled for biologic DMARD treatment were synovectomised by a needle-arthroscopic procedure. Synovial tissue was cultured for 72h, and the concentrations of IL-6, IL-8, MCP-1 and MIP-1b in the culture supernatants were measured by Multiplex immunoassays using heterophilic antibody blocking agents. Spearman rank correlations (r) were calculated for outcome measures using averaged values from the various explant positions. A p-value<0.05 was considered significant. Results: All four mediators were statistically significantly (least significant p-value =0.01) correlated with SJC (r=0.64, r=0.71, r=0.62 and r=0.65 for IL-6, IL-8, MCP-1 and MIP-1b, respectively). IL-6, IL-8 and MCP-1 were highly significantly correlated with TJC (r=0.78, 0.74 and r=0.77, respectively, p=0.001 for IL-8 and p=0.0004 for IL-6 and MCP-1, respectively), whereas MIP-1b had a lower correlation of r=0.58 (p=0.02) for TJC. IL-6 (r=0.58, p=0.02), IL-8 (r=0.56, p=0.03) and MCP-1 (r=0.70, p=0.003) were significantly correlated with DAS-28-CRP. In contrast no statistically significant correlation was found with DAS-28-CRP and MIP-1b (r=0.33, p=0.27) or any of the three mediators with CRP-levels. Conclusions: The production of pro-inflammatory mediators, IL-6, IL-8, MCP-1 and MIP-1b, by synovial explants from RA patients with active arthritis shows a high degree of correlation with clinical disease activity measures. This is indicative of a disease model that can facilitate translation of in vitro findings to in vivo effects. Acknowledgements: Supported by unrestricted grants from Novo Nordisk, The Danish Agency for Science Technology and Innovation and the Oak Foundation. Disclosure of Interest: M. Andersen: None declared, M. Boesen: None declared, K. Ellegaard: None declared, R. Christensen: None declared, K. Söderström Employee of: Nono Nordisk, N. Søe: None declared, P. Spee Employee of: Nono Nordisk, U. Mørch Shareholder of: Nono Nordisk, Employee of: Nono Nordisk, S. Torp-Pedersen: None declared, E. Bartels: None declared, B. Danneskiold-Samsøe: None declared, N. Vendel: None declared, L. Karlsson Employee of: Nono Nordisk, H. Bliddal Grant/research support: Nono Nordisk DOI: 10.1136/annrheumdis-2014-eular.4690